2007
DOI: 10.3892/ijo.30.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification, expression and prognostic role of estrogen- and progesterone receptors in head and neck cancer

Abstract: The aims of this study were to assess the sex hormone receptor status of head and neck (HNC) cancers. Frozen surgical samples (n=67) of HNC patients were analyzed. Protein expression of estrogen receptor (ER)•, ERß and progesterone receptor (PgR) of tumor cells was determined by immunocytochemistry. Data were confirmed at mRNA level by nested-PCR and sequencing. ER and PgR expressions confirmed by PCR analysis were frequent in HNC: 50.7 and 49.3% respectively. Concerning the ER isoforms, ER• expression was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 22 publications
2
63
1
1
Order By: Relevance
“…While a few reports propose the proliferative and anti-apoptotic roles of ERb in cancer cells, the tumor suppressor properties of ERb have been demonstrated by the fact that overexpression of ERb results in anti-proliferative responses, whereas knockdown of ERb promotes the proliferative properties in different cancer cell types (Treeck et al 2007, 2010, Paruthiyil et al 2011, Bossard et al 2012. Moreover, a study of 24 OSCC specimens shows that the frequency of ERa expression (50%) is higher than that of ERb expression (33%) (Lukits et al 2007). In a separate study of HNSCC tumors, the nuclear level of ERa, but not ERb, is significantly higher in the tumor lesions than in paired adjacent normal mucosa (Egloff et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a few reports propose the proliferative and anti-apoptotic roles of ERb in cancer cells, the tumor suppressor properties of ERb have been demonstrated by the fact that overexpression of ERb results in anti-proliferative responses, whereas knockdown of ERb promotes the proliferative properties in different cancer cell types (Treeck et al 2007, 2010, Paruthiyil et al 2011, Bossard et al 2012. Moreover, a study of 24 OSCC specimens shows that the frequency of ERa expression (50%) is higher than that of ERb expression (33%) (Lukits et al 2007). In a separate study of HNSCC tumors, the nuclear level of ERa, but not ERb, is significantly higher in the tumor lesions than in paired adjacent normal mucosa (Egloff et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the expression of ERa and ERb in OSCC tumors and cell lines, and treatment with tamoxifen significantly, inhibits cell proliferation and invasion (Ishida et al 2007, Kim et al 2007, Ku & Crowe 2007, Lukits et al 2007). The expression of ERa and ERb is also found in head and neck squamous cell carcinoma (HNSCC) tumors, but the nuclear levels of ERa, but not ERb, in tumor lesions are significantly higher than that in paired adjacent mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…As they are considered to play important roles in the development of soft tissue lesions [19], sex steroid receptors are widely studied in head and neck tumors [20]. Even though the role of estradiol is known in thyroid cancers, only limited information is available on the role of androgens.…”
Section: Introductionmentioning
confidence: 99%
“…Endocrinal hormones levels in both males as well as females plays a significant role in the etio-pathogenesis and progression of cancers of various organs that are associated with the sex hormones receptor like endometrial carcinoma, breast and prostate cancer, lung carcinoma [10]. Young females associated with certain disorders with hormonal imbalance like Polycystic Ovarian Disease (PCOD), have more potential risk in development of Ovarian cancer and endometrial carcinoma of uterus [11].…”
Section: Introductionmentioning
confidence: 99%